Pengaruh Prestasi Belajar Pengajaran Mikro, Prestasi Belajar Magang Kependidikan 3 dan Keterampilan Mengajar terhadap Kesiapan menjadi Guru Mahasiswa Pendidikan Ekonomi UNS Angkatan 2015 - Annisa Nurul Latifa; Harini Mpd; Budi Wahyono (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2023)
The purpose of this study were (1) to know the effect of micro teaching on the readiness to become teachers of 2015 Economic Education students (2) to find out the effect of micro teaching on 2015 Economic Education students' teaching skills (3) to know the effect of teaching internships 3 on readiness to become teachers 2015 class Economic Education students (4) knew the effect of education internship 3 on the teaching skills of 2015 Economic Education students (5) knowing the effect of teaching skills on the readiness to become a 2015 Economic Education student teacher.In this research quantitative descriptive method was used. The object of this study is the 2015 class of economic education students as many as 60 people. Data collection using questionnaires. The data analysis technique used is Path Analysis. The results of this study (1) micro teaching has a directly effect on the readiness to become a teacher of 2015 Economic Education students (2) micro teaching has a directly effect on the teaching skills of 2015 Economic Education students (3) education internship 3 has a directly effect the readiness to become a teacher of 2015 Economic Education students (4) education internship 3 has a directly effect on the teaching skills of students of the 2015 Economic Education (5) teaching skills directly effect on the readiness to become 2015 Economic Education student teacher.Tujuan dari penelitian ini adalah untuk (1) mengetahui pengaruh pengajaran mikro terhadap kesiapan menjadi guru mahasiswa Pendidikan Ekonomi UNS angkatan 2015 (2) mengetahui pengaruh pengajaran mikro terhadap keterampilan mengajar mahasiswa Pendidikan Ekonomi UNS angkatan 2015 (3) mengetahui pengaruh magang kependidikan 3 terhadap kesiapan menjadi guru mahasiswa Pendidikan Ekonomi UNS angkatan 2015 (4) mengetahui pengaruh magang kependidikan 3 terhadap keterampilan mengajar mahasiswa Pendidikan Ekonomi UNS angkatan 2015 (5) mengetahui pengaruh keterampilan mengajar terhadap kesiapan menjadi guru mahasiswa Pendidikan Ekonomi UNS angkatan 2015.Penelitian ini menggunakkan metode kuantitatif deskriptif. Objek penelitian ini adalah mahasiswa Pendidikan Ekonomi angkatan 2015 sebanyak 60 orang. Pengumpulan data menggunakan kuisioner. Teknik analisis data yang digunakan adalah analisis jalur (Path Analysis). Simpulan dari penelitian ini (1) pengajaran mikro berpengaruh secara langsung terhadap kesiapan menjadi guru mahasiswa Pendidikan Ekonomi UNS angkatan 2015 (2) pengajaran mikro berpengaruh secara langsung terhadap keterampilan mengajar mahasiswa Pendidikan Ekonomi UNS angkatan 2015 (3) magang kependidikan 3 berpengaruh secara langsung terhadap kesiapan menjadi guru mahasiswa Pendidikan Ekonomi UNS angkatan 2015 (4) magang kependidikan 3 berpengaruh secara langsung terhadap keterampilan mengajar mahasiswa Pendidikan Ekonomi UNS angkatan 2015 (5) keterampilan mengajar berpengaruh secara langsung terhadap kesiapan menjadi guru mahasiswa Pendidikan Ekonomi UNS angkatan 2015.Kata Kunci: Prestasi Belajar Pengajaran Mikro, PrestasiBelajar Magang Kependidikan3, Keterampilan Mengajar, Kesiapan menjadi Guru